2000
DOI: 10.1089/088922200750054684
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1nefGene Inhibits Tumor Necrosis Factor α-Induced Apoptosis and Promotes Cell Proliferation through the Action of MAPK and JNK in Human Glial Cells

Abstract: In neurodegenerative diseases associated with AIDS, reactive astrocytosis plays a central role in the neurotoxicity of the brain parenchyma. Whereas the HIV-1 nef gene is overexpressed during restricted HIV-1 infection of human astrocytes, our previous results have demonstrated that nef expressed in human U251MG glial cells activates the sphingomyelin pathway triggered by TNF-alpha, increasing ceramide production. Since ceramide is an important regulatory molecule of programmed cell death induced by TNF-alpha,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…The most dramatic signaling abnormality induced by Nef results from its interaction with the Hck protein tyrosine kinase, resulting in oncogenic transformation of Rat-2 fibroblast (29). Nef induces resistance to tumor necrosis factor-␣-induced apoptosis in U251MG astrocyte cell line through interaction with MAPK and consequently promotes cell growth (30). In our study, the presence of Nef clearly triggers podocyte proliferation and dedifferentiation, growth in soft agar, and focus formation.…”
Section: Discussionsupporting
confidence: 48%
“…The most dramatic signaling abnormality induced by Nef results from its interaction with the Hck protein tyrosine kinase, resulting in oncogenic transformation of Rat-2 fibroblast (29). Nef induces resistance to tumor necrosis factor-␣-induced apoptosis in U251MG astrocyte cell line through interaction with MAPK and consequently promotes cell growth (30). In our study, the presence of Nef clearly triggers podocyte proliferation and dedifferentiation, growth in soft agar, and focus formation.…”
Section: Discussionsupporting
confidence: 48%
“…Calcium/calmodulin (Ca 2+ /CaM)-dependent protein kinases have been shown to regulate mitogen-activated protein kinases (MAPKs) (Enslen et al, 1996). Dysregulated MAPKs have been detected in the central nervous system of SIV-infected macaques (Barber et al, 2004), and it has been shown that Nef modulates MAPK activity in astrocytic U251MG cells (Robichaud and Poulin, 2000). Finally, activated p38 MAPK is necessary for CCL2/MCP-1 expression (Rovin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that sublines expressing wild-type Nef show morphological alterations, increased expression of activation markers (Kohleisen et al, 1999) and increased tumorigenicity in nude mice (Kramer-Hammerle et al, 2001). In addition Nef expression has been shown to protect U251MG cells from TNF-alpha induced apoptosis (Robichaud and Poulin, 2000). These observations suggest that stable expression of Nef alters cellular properties of astrocytes.…”
Section: Introductionmentioning
confidence: 88%